Les regalia du président - Alexandre Girard-Muscagorry (Les Cahiers de l'École du Louvre)
In January 1978, Valéry Giscard d’Estaing, then visiting Yamoussoukro as part of a presidential visit to Côte d’Ivoire, was named Honorary President of the Association of Tribal Chiefs and received, on this occasion, several objects associated with the exercise of power among the Akan peoples of the country. Given by the French presidency to the Musée des Arts Africains et Océaniens and now in the collections of the Musée du Quai Branly – Jacques Chirac, these diplomatic gifts are atypical because of their originality compared to the very standardised corpus of African presidential gifts and the large number of comments they gave rise to throughout their history. In light of the study of the political and diplomatic context in which these objects were created, this article intends to shed light on the motivations that led to their selection, as well as their mixed reception in France under the influence of the political and institutional climate of the period.